2009
DOI: 10.1088/0004-637x/705/1/723
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Abundances of Seven Irregular and Three Tidal Dwarf Galaxies in the M81 Group

Abstract: We have derived nebular abundances for 10 dwarf galaxies belonging to the M81 Group, including several galaxies which do not have abundances previously reported in the literature. For each galaxy, multiple H ii regions were observed with GMOS-N at the Gemini Observatory in order to determine abundances of several elements (oxygen, nitrogen, sulfur, neon, and argon). For seven galaxies, at least one H ii region had a detection of the temperature sensitive [OIII] λ4363 line, allowing a "direct" determination of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
151
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(176 citation statements)
references
References 81 publications
21
151
4
Order By: Relevance
“…The emission lines, therefore, probably originate from gas similar to that found in objects of medium metallicity and low excitation. It is also similar to the Croxall et al (2009) HII regions in tidal dwarf galaxies. Second, the ICL star population is not very old, of the order of 2.3 × 10 9 yr, compared to the BCG population of 9.3 × 10 9 yr (close to estimates of Cui et al 2014, see their Fig.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The emission lines, therefore, probably originate from gas similar to that found in objects of medium metallicity and low excitation. It is also similar to the Croxall et al (2009) HII regions in tidal dwarf galaxies. Second, the ICL star population is not very old, of the order of 2.3 × 10 9 yr, compared to the BCG population of 9.3 × 10 9 yr (close to estimates of Cui et al 2014, see their Fig.…”
Section: Discussionsupporting
confidence: 65%
“…Any of their models with metallicity larger than 1 predict R23 values at least five times smaller than what we observe in the ELDL source. We also compared our results with the work of Croxall et al (2009) on HII regions in dwarf galaxies of the M81 group. From their Fig.…”
Section: Eldl Sourcementioning
confidence: 91%
“…Dwarf galaxies with similarly high metallicity for their luminosity have also been observed in the M 81 group, and it was also suggested that they formed during galaxy interactions in the group from tidal debris (e.g. Croxall et al 2009). Here we aim to test this scenario by studying the integrated properties of the IKN GCs.…”
Section: Introductionmentioning
confidence: 89%
“…Spectroscopy data (line intensities and EW (Hβ)) for IC 2574 are taken from Croxall et al (2009), data for NGC 628 are partly from Gusev et al (2012) and partly from van Zee et al (1998), data for NGC 6946 are taken from Gusev, Sakhibov & Dodonov (2013), and NGC 925 and NGC 3184 data are taken from van Zee et al (1998). Finally, NGC 3621 data are from Ryder (1995).…”
Section: Spectroscopic Datamentioning
confidence: 99%